Two mechanisms of membrane digestion: enzymatic-transport ensemble exists for oligopeptides as well - S. T. Metelsky; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine, which mechanism of dipeptide transport is realized under experimental conditions: PEPT1-mediated transport of the intact dipeptides or transport of the amino acid formed as a result of membrane hydrolysis of dipeptides through transport systems for free amino acid.Material and methods. Amplitudes of short circuit current (SCC) response reflecting rate of Na+-dependent absorbtion of nutrients on addition of dipeptides and amino acids to washing solution at different pH were registered in isolated fragments of the small intestine of rats. Results. Higher efficacy of dipeptide transport (SCC responses to dipeptides were more intensive, than responses to amino acids mixture) was observed at рН 8,5. On the contrary, at рН 5,5 is inverse ratio: stronger SCC responses to amino acid mixture than to dipeptides was revealed. Thus, the explorer, working at рН 5,5, will find, that absorbtion from mixture of aminoacids is more effective, than from dipeptide solution.Conclusions. Increase of sodium-dependent component of stimulating effect of easily hydrolyzed dipeptides along with рН is caused by membrane digestion. Decrease of sodium-independent dipeptide transport component along with рН is related, apparently, to functioning of proton-dependent PepT1 in enterocyte apical membrane. We believe, that such serial «incubation» of gastric contents at increasing рН at gastro-intestinal transit (from the stomach to the large intestine) results in well-timed diversion of two mechanisms of oligopeptide absorbtion and respectively to their optimal digestion.